AgNPs decorated Mg-doped ZnO heterostructure with dramatic SERS activity for trace detection of food contaminants. Issue 27 (4th June 2019) - Yao, Jiacheng; Quan, Yingnan; Gao, Ming; Gao, Renxian; Chen, Lei; Liu, Yang; Lang, Jihui; Shen, He; Zhang, Yongjun; Yang, Lili; Yang, Jinghai
Abstract : Compared with noble metals, semiconductors have been gradually exploited more as another type of SERS substrate materials due to their distinctive advantages. Abstract : Compared with noble metals, semiconductors have been gradually exploited more as another type of SERS substrate materials due to their distinctive advantages. However, an inferior enhancement factor (EF) is a fatal weakness of the semiconductors. So, we combined the strong LSPR coupling between Ag particles and the charge transport channels induced by Mg doping to create a high performance SERS substrate. These magnesium-doped zinc oxide–Ag nanoparticles (ZMOA) exhibited 18 times higher SERS enhancement than when the SERS spectra of 4-MPY was collected on Ag, 30 times higher than magnesium-doped zinc oxide (ZMO), and 121 times higher than ZnO. The formation mechanism and the enhancement mechanism of this substrate were meticulously analyzed and finite difference time domain simulations were used to examine "hot spot" distribution. By using the ZMOA, we could easily achieve the detection limit for malachite green (MG) residue as low as 10 −13 M with a good linear relationship ( R 2 = 0.9914) between the intensity of the SERS signal and the logarithm of the MG concentration, indicating the potential application of the ZMOA substrate in quantitative determination. Also, we employed the proposed ZMOA substrate and established the analytical method for quantitative determination of the residue of MG in fish. The excellent reproducibility, long-term stability, and accuracy of detection make ZMOA a promising substrate for practical detection of contaminants. To the best of our knowledge, this is the first time that remarkable SERS activity has been observed within a hybrid semiconductor, which could open new frontiers for developing highly sensitive and stable SERS technology and has great potential applications in the areas of pesticide residue monitoring, food security, and biotechnology.